ASSOCIATION BETWEEN POLYMORPHISM IN CYTOTOXIC T LYMPHOCYTE ANTIGEN -4 GENE AND THE RISK OF RHEUMATOID ARITHRITIS IN IRAQI PATIENTS - A. A., Rawaa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
CTLA4 is well known that it is expressed in activated T-lymphocyte, and can be distinguished in cancer phenomena as well as many chronic diseases. This study was designed aiming to find a correlation between CTLA-4 and Rheumatoid Arthritis (RA). This research was  carried  out at Baghdad  Teaching  Hospital, Medical  City, Baghdad, Iraq. In this study, 245 patients diagnosed with rheumatoid arthritis and 188 healthy volunteers' individuals (control group) were selected randomly. The diagnosis of the RA to both patients group and healthy individuals were characterized according to a certain protocols. The sequence of four (JO31, CT60, +49, and MH30 genotypes) were carried out using PCR-DGGE. The polymorphisms (SNPs) were genotyped for the control and the patients and the distribution of the genotypes was carried out according to HWE (P